Penyelesaian Sengketa Perkawinan dalam Hukum Keluarga Islam: Peran Lembaga Mediasi dan Arbitrase Syariah di Indonesia - Suci Ramadhan; Faris Maulana Akbar; Abdul Latif (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the role of mediation and arbitration in the settlement of marital disputes within the Indonesian Religious Courts. The main focus is on the effectiveness and contribution of these two mechanisms in realizing fast, cheap, and civilized justice as mandated in the Islamic family law system. Qualitative methods were used with normative-juridical and sociological approaches, supported by document studies and interviews with judicial practitioners. The results showed that although mediation has a strong legal framework in Supreme Court Regulation (Perma) Number 1 Year 2016, its implementation still faces cultural and structural challenges. Meanwhile, arbitration has not been widely utilized in family disputes despite its potential as an alternative to deliberation-based conflict resolution. Mediation is the dominant and effective dispute resolution mechanism in the Religious Courts, with a fairly high success rate in resolving marital conflicts. Arbitration, although less popular, also has significant potential in resolving disputes, particularly in cases involving financial disputes or joint property. The role of mediators and arbitrators is crucial in facilitating amicable agreements and maintaining good relations between the parties. Mediation and arbitration are important instruments in Indonesia's religious justice system for resolving marital disputes. The application of these two mechanisms is in line with the principles of Islamic family law which emphasize peaceful resolution of conflicts and maintaining the integrity of the household. Their effectiveness depends on the competence of the mediators and arbitrators, as well as the commitment of the parties to reach a fair and equitable settlement.